Quantitative analysis of SLC34A2 expression in different types of ovarian tumors - Shyian, M.; Gryshkova, V.; Kostianets, O.; Gorshkov, V.; Goloev, Yu.; Goncharuk, I.; Nespryadko, S.; Vorobjova, L.; Filonenko, V.; Kiyamova, R. (Experimental Oncology, 2011)
Aim: The main purpose of this study was to estimate the SLC34A2 gene expression in normal ovary and different types of ovarian tumors. Methods: We have investigated SLC34A2 gene expression level in papillary serous, endometrioid, unspecified adenocarcinomas, benign tumors, and normal ovarian tissues using real-time PCR analysis. Differences in gene expression were calculated as fold changes in gene expression in ovarian carcinomas and benign tumors compared to normal ovary. Results: We have found that SLC34A2 gene was highly expressed in well-differentiated endometrioid and papillary serous ovarian carcinomas compared to low-differentiated endometrioid carcinomas, benign serous cystoadenomas and normal ovary. Analysis of SLC34A2 gene expression according to tumor differentiation level (poor- and well-differentiated) showed that SLC34A2 is up-regulated in well differentiated tumors. Conclusion: Upregulation of SLC34A2 gene expression in well-differentiated tumors may reflect cell differentiation processes during ovarian cancerogenesis and could serve as potential marker for ovarian cancer diagnosis and prognosis.